2017
DOI: 10.1590/1980-5497201700010011
|View full text |Cite
|
Sign up to set email alerts
|

Fatores sociodemográficos e capacidade funcional de idosos acometidos por acidente vascular encefálico

Abstract: Introduction: Diseases of old age have shown increasing prevalence in society. One of them is stroke, which can be conceptualized as the interruption of cerebral blood supply due to a leakage or blood vessel obstruction caused by clots. Objective: To verify the associations between sociodemographic factors and the functional capacity of elderly affected by stroke. Methods: This is an epidemiological, cross-sectional, and quantitative study, including 118 elderly people with paralyses due to stroke, who were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
1
0
8
Order By: Relevance
“…In addition, national and international studies have found high prevalence rates of functional disability in diabetic older adults after a cerebrovascular event (Carmo et al, 2016;Dutra et al, 2017). This relationship is explained by the vascular damage caused by diabetes itself and other lifestyle factors which, when combined, predispose older adults to higher levels of systemic inflammation and damages to the integrity of the various organs, thereby compromising functional capacity (Rekeneire & Volpato, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, national and international studies have found high prevalence rates of functional disability in diabetic older adults after a cerebrovascular event (Carmo et al, 2016;Dutra et al, 2017). This relationship is explained by the vascular damage caused by diabetes itself and other lifestyle factors which, when combined, predispose older adults to higher levels of systemic inflammation and damages to the integrity of the various organs, thereby compromising functional capacity (Rekeneire & Volpato, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Este estudo teve como objetivo analisar a independência funcional dos pacientes pós-AVC que utilizam as técnicas de reabilitação cinesioterapia e RVNI. Esta análise mostra-se relevante no planejamento da reabilitação dos pacientes pós-AVC, pois observa-se prejuízo na capacidade funcional desses indivíduos [12].…”
Section: Discussionunclassified
“…Justifica-se a prevalência dos AVE em pessoas mais idosas como sendo o grupo com maior índice de hipertensão arterial, que caracteriza-se como um fator de risco para o desenvolvimento deste episódio. Desta forma, identifica-se a necessidade das estratégias voltadas à prevenção das doenças e promoção da saúde para poder obter um controle mais efetivo [13] Relacionado ao acometimento por sexo, obteve-se um valor maior no sexo feminino, outros estudos mostraram em seus resultados que em relação a este fator de risco não modificável, existe um predomínio maior nas mulheres [12,14] não foi observado diferenças discrepantes em relação ao sexo feminino ou masculino. Os autores mencionam que tal fator, colabora para confirmação de que não existe uma necessidade de elaborar políticas públicas que sejam diretamente direcionadas a subpopulação especificamente de homens e mulheres no que direciona às terapêuticas e mudanças de comportamento.…”
Section: Discussionunclassified